Analysis on the Development of Digital Governance and Collaborative Citizen Participation in the Field of Public Administration - Siyi Wang (International Journal of Social Sciences and Public Administration, 2026)
Digital technology is continuously changing the operating logic of public administration, and citizen participation in building and running digital governments has been used to measure the effectiveness of government digitalisation. The current development situation of citizen collaborative participation in the field of public administration will be examined through three lenses in this paper: institutional supply, platform support and practical operation. The national integrated government service platform has more than 1.08 billion registered users, and there are a total of 13,440 government websites and 82,151 government new media accounts at all levels in the country. Promptly respond to the public's complaints and enhance other modes of government-citizen communication. The State Council's "Guiding Opinions on Strengthening Digital Government Construction" has listed "prompt response to public complaints" as one of the key new forms of Digital Government Construction. Digital Infrastructure and institutional frameworks have provided the initial support for citizen participation. Obstacles to online participation still exist, data security risks are present, and the efficiency of some platform interactions is relatively low; thus, the scale and depth of collaboration have not been maximized. In the interest of promoting high-quality development of digital governance and citizen participation, efforts should be made to coordinate technological empowerment and institutional innovation, focus on the simultaneous progress of expanding participation channels and improving the effectiveness of participation, manage the relationship between data openness and the limits of privacy protection, and build a governance pattern where technology and institutions work together.